Intensity Distribution of Partially Coherent Array Finite Airy Beams Propagating in Atmospheric Turbulence - Jin, Long; Zhang, Zirui; Wang, Nuo; Liu, Zixin; Deng, Yuwei; Fu, Yanhua (International Journal of Optics, 2021)
Based on the extended Huygens–Fresnel integral and the Rytov phase structure function, the closed-form expression of a partially coherent array finite Airy beams (PCAFABs) cutting through the Kolmogorov atmospheric turbulence is derived in the space domain under the paraxial approximation. The characteristics of the PCAFABs evoluting in the atmospheric environment are investigated in detail on the basis of the derived wave propagation formulae. We mainly illustrate the intensity profile of this beam changed with the truncation parameter, coherence length, and turbulence factor at several cross sections of the atmospheric space by means of numerical figures. It is convinced that the present concept and derived conclusions will provide useful exploration for learning the optical properties of the PCAFABs transmitting in the atmospheric turbulence, especially for free-space optical communication area.